Perubahan Dalam Pendidikan Perspektif Al Qur’an Dan Hadits Tarbawi - Mutia Isfah Ardilah; Rahendra Maya (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study examines the concept of change (al-taghyir) in Islamic education and its implications for contemporary educational practices. The background of this research is rooted in the dynamic nature of social change, which requires educational systems to remain adaptive while preserving spiritual values. This research employs a library research method by analyzing sources from the Qur’an, Hadith, and relevant academic literature. The findings reveal that, from an Islamic perspective, educational change is not solely oriented toward cognitive development but also encompasses spiritual, moral, and social dimensions through the integration of tarbiyah, ta’lim, and ta’dib. Prophetic traditions (hadith tarbawi) provide a gradual, contextual, and practical approach to change, aligned with learners’ developmental stages, ranging from pedagogical to heutagogical approaches. The implications for contemporary education include curriculum transformation, digitalization of learning, character strengthening, and improving the quality of educational systems. Thus, Islamic education serves as an agent of change that fosters a balance between knowledge, faith, and social responsibility.